Batch solvent extraction of caffeine from MCBC2 - Nedunjeliyan, Dinesh Varma (2010)
Caffeine is a naturally occurring substance found in cocoa seeds. The aim of this research is to extract caffeine from Malaysian Cocoa Board Clone (MCBC) 2, and to investigate the effect of sample particle size, solvent/feed ratio, and extraction time on the yield of caffeine. The sample was prepared by grinding and sieving, followed by solid-liquid extraction using water by heat reflux extracting technique, liquid-liquid extraction with ethyl acetate, drying of caffeine by rotary evaporator, and finally analysis of the caffeine yield. The analysis of the caffeine yield was done using UV/Vis Spectrophotometric method. The caffeine yield was highest at sample particle size of 400µm (0.35 % w/w caffeine or 3.4956 mg/g cocoa), solvent/feed ratio of 1:1 (0.35 % w/w caffeine or 3.5066 mg/g cocoa), and extraction time of 90 minutes (0.34 % w/w caffeine or 3.4356 mg/g cocoa). The best conditions for the highest yield of caffeine from MCBC2 were 400µm of sample particle size, 1:1 of solvent/feed ratio, and 90 minutes of extraction time.